M&As motives and target evaluation : A case study in shipbuilding - Merla, Niklas (My University, 2025)
Mergers and acquisitions (M&A) have been studied extensively in international business literature. Some of the most commonly researched topics include M&A motives as well as strategic and cultural fit. However, major questions remain within this field of research. Namely, the high failure rates of M&As, commonly cited in literature, indicate that this area of research is still not fully understood. To combat this issue, more holistic M&A frameworks have been suggested as a potential answer. In this thesis, the subject of M&As is studied in the context of the shipbuilding industry. In particular, a case study within a Finnish shipyard is conducted to determine, whether M&A is the right strategical tool for solving a particular business problem. Namely, it is determined whether M&A can be used as a means for improving efficiency within the case company. To answer this question, an augmented business evaluation framework is used. In this model, the strategic motives and objectives regarding M&A are combined with the existing framework developed by Hassan and colleagues (2016). Within the augmented framework, potential target companies are identified and evaluated using three stages: target selection, target valuation, and performance assessment. The empirical section of this study is conducted using a qualitative approach. In particular, an intensive case study is conducted to answer the research question. The data for this study consists of semi-structured interviews as well as secondary data. The interviews were conducted with employees from the case company. The secondary data, on the other hand, consists of internal as well as publicly available documents. The empirical data was analyzed using two methods: thematic analysis and qualitative content analysis. The results of this study indicate that challenges within the practical level can make or break a theoretically sound M&A plan. In particular, this study emphasizes the importance of conducting initial target evaluation at the early stages of the M&A process. According to the findings of this study, suitable target candidates can be difficult to determine if attributes uncommon for the industry are required. Further, the M&A process can be hindered by change resistance and lack of clear scope for the deal. Interestingly, this study also indicates that the perceptions of fit between the acquirer and the target can vary significantly across the different functions within an organization. In other words, the perceptions of strategic and organizational fit are not always consistent across the entire organization.

Fuusioita ja yritysostoja on tutkittu laajasti kansainvälisen liiketoiminnan kirjallisuudessa. Yleisimpiä tutkimusaiheita ovat muun muassa yrityskauppojen motiivit sekä strateginen ja kulttuurinen yhteensopivuus. Tutkimusalalla on kuitenkin edelleen suuria kysymyksiä. Kirjallisuuden mukaan suuri osa yrityskaupoista epäonnistuu. Tämä osoittaa, että tutkimusalue ei ole vielä täysin ymmärretty. Ongelman ratkaisemiseksi onkin ehdotettu muun muassa kattavampia yrityskauppojen viitekehyksiä. Tässä Pro gradu -tutkielmassa yrityskauppoja tutkitaan laivateollisuuden kontekstissa. Tutkimus suoritettiin tapaustutkimuksena eräälle suomalaiselle telakalle. Sen tarkoituksena on selvittää, onko case-yrityksen kannattavaa hyödyntää yrityskauppoja tietyn liiketoimintaongelman ratkaisemiseksi. Tarkemmin ottaen, voitaisiinko yrityskauppoja hyödyntää tehokkuuden parantamisen keinona. Tutkimuksessa hyödynnetään laajennettua kohdeyritysten arvioinnin viitekehystä. Pohjana viitekehykselle toimii Hassanin ja kollegoiden (2016) kehittämä kohdeyritysten arvioinnin viitekehys. Laajennetussa viitekehyksessä mahdolliset kohdeyritykset tunnistetaan ja arvioidaan kolmessa vaiheessa: kohteen valinta, kohteen arviointi ja suorituskyvyn arviointi. Tämän tutkimuksen empiirinen osa on toteutettu kvalitatiivisella menetelmällä, intensiivisenä tapaustutkimuksena. Tutkimuksen aineisto koostuu puolistrukturoiduista haastatteluista sekä sekundaarisista aineistoista. Haastattelut toteutettiin case-yrityksen työntekijöiden kanssa. Sekundaarinen aineisto puolestaan koostuu sisäisistä sekä julkisesti saatavilla olevista asiakirjoista. Tutkimusaineisto analysoitiin kahdella menetelmällä: teemoitteluanalyysillä sekä kvalitatiivisella sisällönanalyysillä. Tämän tutkimuksen tulokset osoittavat, että käytännön haasteet voivat vaikuttaa merkittävästi yrityskauppojen toteuttamiseen, vaikka yrityskaupat vaikuttaisivatkin kannattavilta teoreettisella tasolla. Tämä tutkimus korostaa erityisesti kohdeyritysten alustavan arvioinnin merkitystä. Tutkimustulokset osoittavat, että sopivien kohdeyritysten löytäminen voi olla vaikeaa, jos kohdeyritykseltä vaaditaan toimialalle epätyypillisiä ominaisuuksia. Lisäksi muun muassa muutosvastarinta ja selkeän strategian puute voivat vaikeuttaa yrityskauppaprosessia. Tämän tutkimus myös osoittaa, että yrityksen eri osastoilla saattaa olla hyvin erilainen kuva ostajan sekä kohdeyrityksen strategisesta ja kulttuurisesta yhteensopivuudesta.
Keywords: M&A, Business evaluation, Case study, fuusiot ja yrityskaupat, evaluaatio, tapaustutkimus